SARS-CoV-2 S Protein Subunit 1 Elicits Ca2+ Influx – Dependent Ca2+ Signals in Pancreatic Stellate Cells and Macrophages In Situ. Issue 2 (31st January 2022) - Gerasimenko, Julia V; Petersen, Ole H; Gerasimenko, Oleg V
Abstract: The S protein subunit 1 (S1) of SARS-CoV-2 is known to be responsible for the binding of the virus to host cell receptors, but the initial intracellular signalling steps following receptor activation of cells in the exocrine pancreas are unknown. Using an intact live mouse pancreatic lobule preparation, we observed that S1 elicited Ca 2+ signals in stellate cells and macrophages, but not in the dominant acinar cells. The Ca 2+ signals occurred mostly in the form of repetitive Ca 2+ spikes. The probability of observing Ca 2+ signals depended on the S1 concentration. The threshold was close to 70 nM, whereas at 600 nM, all cells responded. The SARS-Cov-2 nucleocapsid protein did not elicit any Ca 2+ signals in any of the three cell types tested. The S1-induced Ca 2+ signals in stellate cells started much faster (122 ± 37s) than those in macrophages (468 ± 68s). Furthermore, the interleukin-18 binding protein (IL-18BP) abolished the responses in macrophages without affecting the Ca 2+ signals in stellate cells. The S1-elicited Ca 2+ signals were completely dependent on the presence of external Ca 2+ and were abolished by a selective inhibitor (CM4620) of Orai1 Ca 2+ Release Activated Ca 2+ channels. SARS-CoV-2 may contribute to acute pancreatitis, an often fatal inflammatory human disease. The S1-elicited Ca 2+ signals we have observed in the pancreatic stellate cells and endogenous macrophages may play an important part in the development of the inflammatory process. Graphical Abstract: